2017
DOI: 10.1002/ca.23007
|View full text |Cite
|
Sign up to set email alerts
|

The facial artery

Abstract: The facial artery is the major vessel supplying blood to the face so its location and course are very important for the safe manipulation of both surgical and non‐surgical interventions. This study documents current anatomical information about the facial artery and its tributaries. The terminology of the facial artery tributaries was revisited with reference to the Terminologica Anatomica and novel nomenclature was suggested with anatomical features. The tributaries to the lower lip (inferior labial artery), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 34 publications
0
27
0
1
Order By: Relevance
“…In 2014, Yang et al reported that in 93.3% the branch of the FA proceeded around the NLF and was located 3.2 ± 4.5 mm and 13.5 ± 5.4 mm lateral to the nose alar and oral commissure, respectively. Also, the detoured branch stretched along the lower edge of the orbicularis oculi muscle 27 …”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Yang et al reported that in 93.3% the branch of the FA proceeded around the NLF and was located 3.2 ± 4.5 mm and 13.5 ± 5.4 mm lateral to the nose alar and oral commissure, respectively. Also, the detoured branch stretched along the lower edge of the orbicularis oculi muscle 27 …”
Section: Discussionmentioning
confidence: 99%
“…The anatomy of the FA was recently reviewed, being documented that the inferior labial a. it either branches at the cheilion and courses long the vermilion border of the inferior lip, or it branches below the cheilion and courses along the labiomental crease as an horizontal labiomental artery [17], such as in the Case #2 reported here. The inferior labial artery and the horizontal labiomental artery are the main arteries used in the lower lip pedicle [18].…”
Section: The Labiomental Trunkmentioning
confidence: 88%
“…The face has an extensive vascularity with numerous communicating branches between both direct and indirect linking vessels in the coronal, sagittal, and transverse planes. 39,40 These communicating branches consist of 2 quite distinct and different types of arteries. The first type of interconnections is less frequent and consists of vessels that are constant in caliber: the true anastomoses.…”
Section: Discussionmentioning
confidence: 99%